The effects of intermittent fasting on anthropometric indices, glycemic profile, chemotherapy-related toxicity, and subjective perception in gynecological and breast cancer patients: a systematic review and meta-analysis - Xiaoxia Liu; Qiucen Meng; Wenqi Fan; Lianzhen Ning; Lina Ge (BMC Cancer)
Abstract Background Mounting evidence supports the health benefits of intermittent fasting (IF) in general. This study evaluates its impact on patients with gynecological or breast cancer specifically. Methods A thorough search for studies comparing IF with either nonintervention diets or calorie restriction (CR) in patients with either gynecological or breast cancer and published prior to October 5, 2024 was carried out on the PubMed, Web of Science, Cochrane Library, Scopus, Embase, China National Knowledge Infrastructure (CNKI), and Chinese Biomedical Literature databases (CBM). Extracted data included but not limited to body mass index (BMI), body weight, waist circumference (WC), fasting glucose, insulin levels, chemotherapy-related toxicity, and subjective perceptions. Results A total of 625 subjects were included across 7 randomized controlled trials, and 2 nonrandomized trials. Meta-analysis revealed that IF significantly reduced body weight (Effect Size [ES]: -0.611; 95% Confidence Interval [CI]: -0.886 to -0.356; p < 0.001; I² = 0%), blood glucose levels (standardized mean difference [SMD]: -0.347 mmol/L; 95% CI: -0.533 to -0.140; p < 0.001), and insulin concentrations (SMD: -0.395 mU/L; 95% CI: -0.674 to -0.116; p = 0.005). Sensitivity analysis indicated that the overall effect sizes were stable. However, it remains uncertain whether IF increases chemotherapy-related adverse effects (relative risk [RR]: 1.038; 95% CI: 0.844 to 1.278; p = 0.723). Furthermore, three studies indicated that IF reduced fatigue and two studies indicated that IF improved quality of life. Conclusion This systematic review and meta-analysis suggests that IF has a beneficial effect on reducing body weight, blood glucose, and insulin concentrations in gynecological and breast cancer patients. IF may also reduce fatigue and improve quality of life. However, the effect on chemotherapy-related adverse effects is uncertain. Further high-quality studies with long-term follow-ups are needed to confirm these findings.